2019
DOI: 10.1002/cam4.2421
|View full text |Cite
|
Sign up to set email alerts
|

Effect of IDH3a on glucose uptake in lung adenocarcinoma: A pilot study based on [18F]FDG

Abstract: Subunit of isocitrate dehydrogenase 3 (IDH3a) as upstream of the hypoxia‐inducible factor was reported highly expressed in malignant tumors, playing an important role in glucose metabolism reprogramming. As one of rate‐limiting enzyme in the Krebs cycle, whether high expression of IDH3a affects glucose uptake in tumors has not been elucidated. This study was aimed to investigate the relationship between IDH3a expression and tumor glucose uptake. Sixty‐five patients who underwent 2‐[ 18 F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…This indicated that the metabolic and epigenetic changes were intertwined and highly dependent on miR–9-5p expression in trained immunity. Diminished IDH3 activity results in the metabolic switch from oxidative phosphorylation to glycolysis ( 30 ). IDH3α inactivation reduced the ratio of α-KG to fumarate and succinate ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that the metabolic and epigenetic changes were intertwined and highly dependent on miR–9-5p expression in trained immunity. Diminished IDH3 activity results in the metabolic switch from oxidative phosphorylation to glycolysis ( 30 ). IDH3α inactivation reduced the ratio of α-KG to fumarate and succinate ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…The composing α, β, and γ subunits of HsIDH3 play distinct roles in the assembly, catalytic reaction, and allosteric regulation of the holoenzyme. Mutations and dysregulation of different subunits of HsIDH3 have been associated with various diseases including cancers ( 26 , 27 , 28 ). Therefore, the functional, structural, and mechanistic studies of HsIDH3 have important biological and biomedical significances.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin has been previously shown to synergize the augmentation of ROS level by anticancer drugs (47). SDH and IDH3A have been implemented in the regulation of ROS generation in malignant pathologies (48), chemoresistance (49), glucose uptake (50), and invasion (51). Curcumin was able to induce SDH expression and repress the IDH3a in HepG2 cells both in normal or elevated level of glucose.…”
Section: Discussionmentioning
confidence: 99%